The Translation of Ὑποκριτης in the Gospels as Osatotsε in Dangme Bible Translations - Ebenezer Quaye; Jonathan Edward Tetteh Kuwornu-Adjaottor (Journal of Mother-Tongue Biblical Hermeneutics and Theology)
Translating from one language to another is a difficult task. Words, phrases and other expressions are socio-culturally or contextually defined and more so, they assume new meanings through both diachronic and synchronic time effects. The nuances in meaning when ideas are carried from one linguistic setting to another is another challenge in translation work. This becomes more challenging when one attempts to find equivalences in translations. This work looks at the word, osatotsε, being the Dangme word for the Greek, ὑποκριτης of the biblical text, especially, in the gospels. Osatotsε (O sa [kε]to tsε) in Dangme, literally or basically means “rotten (spoilt) but hidden owner (person).” Although this translation for all intents and purposes largely fits the contexts in which it is used, especially in the gospels, it does not fully translate the word, ὑποκριτης. This basically affects the interpretation of the texts in which osatotsε finds itself in terms of meaning and usage. This paper discusses ὑποκριτης and osatotsε by using lexical analysis and the mother-tongue to underscore the challenge of equivalence of translating words from one language into another. It emphasizes the need for a corresponding footnote (commentary) in subsequent publications of the Dangme Bible, Ngmami KlϽuklϽu Ͻ to the word, osatotsε to make its usage in preaching and teaching more efficient and effective. This work seeks to redefine the meaning of ὑποκριτης in Dangme translations although osatotsε, to a large extent but not absolutely, fits the contexts in which it is used in biblical texts, especially, in the gospels. This paper, therefore, puts forward that ὑποκριτης is a broader terminology as compared to osatotsε as an equivalence in Dangme translations.